Replik - Metzinger, Thomas (Zeitschrift für Theologie und Philosophie, 2026)
In this reply, I address the critical objections raised by Charlotte Gauvry, Stefan Lang, Mona Schramke, Alexander Knoll, Patricia Schöllhorn-Gaar, Sebastian Gäb and Klaus Viertbauer. I aim to provide a deeper understanding of the concept of Minimal phenomenal Experiences (MPE) by taking part in the critical, yet constructive discussion of this approach.